Narrativas autobiográficas de professores universitários acerca do cinema como experiência formadora da docência - Oliveira, Antonio Ivanilo Bezerra de (2023)
During my academic career, I have studied the use of films in school environments. Affected by these studies, my interest now concerns the teacher trainers, that is, university professors who work in undergraduate teaching courses and who mobilize cinema films in their formative practices, based on the premise: teachers, when using cinema in their practices, do not detach themselves from their personal experiences, since the adoption of film language is not common in the courses’ curricula. Thus, the general objective of the research is to understand the implications of cinema in the constitution and practice of teaching, present in the autobiographical narratives of professors who work in undergraduate teaching courses. To this end, I use the following concepts: formative experience, aiming to understand how cinema crossed the lives of teachers; autobiographical narratives, which concern the effort of elaboration and synthesis of the experiences lived by individuals; and cinema as a formative device, intending to discuss how films are thought and mobilized in the activities developed by the teacher trainers. As for the methodological framework, the investigation is centered on the qualitative approach and employs the method of (auto)biographical research in Education, with the narrative interview as main technique of construction of its corpus, which was conducted with 10 teacher trainers, whose narratives were analyzed according to the methodological procedures proposed by the discursive textual analysis. The research showed that the films are part of the participants’ life history, enabling the construction of formative experiences that helped them in their personal and professional growth. Regarding the repercussions of these experiences on the participants’ practice, we concluded that cinema appears as a privileged training device, used intentionally in their practices, helping them in training critical, reflective teachers, knowledgeable about techniques necessary for pedagogical work and attentive to the subjectivities that involve the act of teaching and learning.